Lean construction at construtora x: a case study on waste elimination and productivity improvement - Camargo, João Vinícius Grama; César, Cristina Guimarães; Nunes, Felipe Alexandre de Souza Félix; Pontífice, Sabrina Godinho; Gonçalves, Carlos Alberto (Brazilian Journal of Production Engineering, 2024)
Context: The construction sector in Brazil faces challenges related to efficiency, costs, and sustainability. In this context, the implementation of the Lean Construction philosophy is an alternative to optimize processes, reduce waste, and increase productivity. Objective: The objective of this study is to analyse the impact of adopting the Lean Construction methodology in a company in the Brazilian construction sector, focusing on the benefits related to efficiency and sustainability. Method: The research is a case study in a company that adopted Lean practices, using both qualitative and quantitative approaches, including a survey and analysis of employees’ responses to a questionnaire, as well as interviews with managers and performance indicator analysis. Results: The results indicate a perceived reduction in waste, improvements in process efficiency, and a positive impact on the sustainability of the analysed company’s operations. Conclusion: The adoption of the Lean Construction philosophy in the construction sector presents itself as a promising strategy to increase competitiveness, improve efficiency, and contribute to sustainability.